Employing smart interactive architecture techniques to improve the internal and external environment of public libraries in Egypt | توظيف تقنيات العمارة التفاعلية الذكية في تحسين البيئة الداخلية والخارجية للمكتبات العامة في مصر - Al Naqib | النقيب , Metouali Mahmoud | متولي محمود; Ismail | إسماعيل , Nihal Fouad | نهال فؤاد (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
The study aims at finding out the extent to which smart interactive architecture techniques are employed in enhancing the internal and external environment of public libraries in Egypt in light of the requirements of transition towards smart libraries and sustainable development. The study presents and analyzes the most important techniques of smart interactive architecture used globally. These techniques can support the design of library buildings in Egypt and raise the level of smart public library buildings to achieve their competitiveness and sustainability. The study attempts to answer the following main question: What is the extent of employing smart interactive architecture techniques in enhancing the internal and external environment of public libraries in Egypt? To achieve the objectives of the study, the researchers used the descriptive analytical method in its survey style, which studies the phenomenon by describing it in reality through verifying the hypotheses. The study population consists of three categories: library specialists, engineers and technicians working in the engineering department from which the library is affiliated, and library users. The field study was applied to a random stratified sample of these categories in public libraries in the governorates of Cairo, Giza, and Alexandria. The importance of the study is to provide the mechanisms necessary to transform library buildings into smart interactive architectural buildings in order to achieve the quality of the internal and external environment for these buildings’ occupants and collections. | تهدف الدراسة إلى معرفة مدى توظيف تقنيات العمارة التفاعلية الذكية في تعزيز البيئة الداخلية والخارجية للمكتبات العامة بمصر في ضوء متطلبات التحول نحو المكتبات الذكية والتنمية المستدامة، مع عرض وتحليل لأهم تقنيات العمارة التفاعلية الذكية المستخدمة عالميا، والتي يمكن أن تدعم تصميم مباني المكتبات في مصر، ومن ثم رفع مستوى ذكاء مباني المكتبات العامة بما يحقق قدرتها على التنافسية والًاستدامة. وذلك من خلال الإجابة عن التساؤل الرئيس الآتي: ما مدي توظيف تقنيات العمارة التفاعلية الذكية في تعزيز البيئة الداخلية والخارجية للمكتبات العامة بمصر؟ ولتحقيق أهداف الدراسة قام الباحثان باستخدام المنهج الوصفي التحليلي بأسلوبه المسحي للتحقق من عدد من الفرضيات. ويتكون مجتمع الدراسة من ثلاث فئات، فئة اختصاصيي المكتبات، وفئة المهندسين والفنيين العاملين بالإدارة الهندسية التي تَتْبعها المكتبة، وفئة المترددين في المكتبات العامة بمحافظات القاهرة، والجيزة، والإسكندرية. وتتمثل أهمية الدراسة في تقديم الآليات اللازمة لتحويل مباني المكتبات إلى مبان معمارية تفاعلية ذكية بما يحقق جودة البيئة الداخلية والخارجية لشاغلي هذه المباني وما تحتويه من مقتنيات.